Intervertebral Disc Extrusion between T8 and T9 in a Dachshund - Diamante, Gabriel Antonio Covino; Marinho, Paulo Vinicius Tertuliano; Zani, Carolina Camargo; Elias, Bruno Cesar; Arias, Mônica Vicky Bahr (Acta Scientiae Veterinariae, 2016)
Background: Intervertebral disc extrusion with consequent spinal compression or intervertebral disc disease (IVDD) is one of the most common causes of compressive myelopathy in dogs, and the thoracolumbar spine discs between T12 and L2 are most affected. Extrusions in cranial thoracic region are rare, and there is few cases in literature reporting this situations, this rarity is attributed to the presence of the intercapital ligament connecting the rib heads between T2 and T10, which strengthens this region both mechanically and anatomically. The aim of this article is report the clinical signs, diagnosis and treatment of a case of Type I Hansen IVDD between T8 and T9 in a Dachshund breed dog. Case: An 8-year-old Dachshund male dog was presented for investigation of pelvic limb incoordination and back pain, which started 10 days prior to the consultation. It had a history of a similar condition 3 months earlier that showed improvement after clinical treatment. On neurological examination was identified in both pelvic limbs proprioceptive ataxia, absence of proprioception, increased muscle tone, presence of interdigital reflex and increased patellar reflex. Cutaneous trunci reflex was absent below T11 on the left side, and pain was noted upon palpation of T7 through the T12 vertebrae. A grade II asymmetric thoracolumbar lesion with hyperesthesia was diagnosed. On suspicion of IVDD, cerebrospinal fluid (CSF) collection and CT scan analysis of the thoracolumbar region were performed. CT scan showed the presence of hyperattenuating and mineralized material, 1 cm long, on the floor of the spinal canal, mainly on the left side, occupying 80% of the diameter of the spinal canal between T8 and T9. The patient was then submitted to decompression surgery through hemilaminectomy and showed a good recovery. As the occurrence of disc extrusion in cranial thoracic region of chondrodystrophic breeds is rare, we report the clinical signs, diagnosis and treatment of a case of Type I Hansen intervertebral disc disease (IVDD) between T8 and T9 in a Dachshund breed dog. Discussion: All spinal discs can undergo a process of degeneration causing IVDD, in which the cervical and thoracolumbar regions are the most affected due to reasons not yet fully understood, however spinal cord compression between the T1 and T9 vertebrae is very rare, probably due to the strengthening provided by the intercapital ligament to the posterior annulus fibrosus. Disc extrusion in unusual locations in chondrodystrophic breeds is mainly reported as extrusion between vertebrae T1 and T2, and T9 and T10, with some cases was attributed to an anatomical abnormality of the intercapital ligament. The evaluation of intervertebral discs of the German shepherd breed dogs using MRI showed disc degeneration processes in thoracic vertebras. Disc extrusions often result in more severe clinical signs than protrusions, and occur acutely or subacutely, which was different from the case described here, maybe because the presence of the intercapital ligament permitted gradual extrusion allowing the spinal cord to adapt to the compression. Despite surgical access to this region being described as more complex due to the presence and proximity of the rib head to the vertebral body and the possibility of injuring the intercostal muscles causing pneumothorax, the hemilaminectomy and rib head excision at T9 could be performed without any complications. Thus, although unusual, the cranial thoracic region should not be overlooked as a possible site of occurrence of IVDD, since the diagnosis, treatment and prognosis are similar to those in patients with extrusions in the most common sites. Keywords: intervertebral disc degeneration, dogs, paresis, ataxia.